Numerical Study of the Solid Particle Erosion on H-Type Finned Circular/Elliptic Tube Surface (Communications in Computational Physics, 2018)
In this paper, numerical simulations of solid particle erosion phenomena onH-type finned circular/elliptic tube surface, which is of great significance to the antiweardesign of heat exchanger, are presented. The Eulerian-Lagrangian approach isapplied to simulate the dilute gas-solid flow through H-type finned circular/elliptictubes. A semi-empirical model is adopted to predict the erosion rate. The dynamicsbehavior of the entrained solid particles in the flow is presented. The geometry oferoded tube surface is changed with the predicted erosion which is taken into accountby a UDF and the flow field is re-solved for the eroded tube surface at every time step.The influences of ten parameters (the tube bundle arrangement, particle size, particleconcentration, fluid Reynolds number, fin thickness, fin pitch, fin length, fin width,slit width and the transverse tube pitch) on the maximum erosion depth of the H-typecircular/elliptic finned tube surface are investigated. Using H-type finned elliptic tubesurface can effectively reduce the erosion rate of tube surface compared with that usingH-type finned circular tube surface. The erosion in in-line arrangement is less severethan that in staggered arrangement. With the increase of particle size, particle concentrationand the fluid Reynolds number, the erosion rate of the tube surface rises. Thenumerically predicted effect of Reynolds number is in good agreement with previoustest data. Among the six geometry parameters, the most influential parameter is thetransverse tube pitch.